Chapter 15. Root Crop Production in Florida - Julien Beuzelin; Peter J. Dittmar; Richard N. Raid; Hugh A. Smith; Bonnie Wells; Johan Desaeger; Lincoln Zotarelli; Shouan Zhang; Qingren Wang; Craig Frey (EDIS, 2021)
Chapter 15 of the Vegetable Production Handbook.